THE EFFECTIVENESS OF CALLIGRAPHY ON MAHARAH AL-KITABAH OF QUR'AN MEMORIZERS AT MADRASAH TSANAWIYAH MA'HAD TAHFIZHIL QUR'AN ISLAMIC CENTER FOUNDATION OF NORTH SUMATERA - Aqilah Fitriah Jala; Nadila Nadila (Yayasan Haiah Nusratul Islam, 2024)
Maharah al-kitabah (calligraphy) has a very important role as a support in Islamic educational institutions, especially in the writing of the Qur'an. However, there are problems that are often found among students, they experience difficulties when dealing with writing Arabic script according to calligraphy rules and even the level of writing proficiency is also very low. This is found in the Ma'had Tahfizhil Qur'an Islamic Center Foundation SU, one of the modern-based Islamic boarding schools that prints thousands of memorizers of the Qur'an (Haafizul Qur'an). This study aims to find a comprehensive understanding according to the title studied by the researcher. The research methodology is a type of qualitative descriptive method, namely literature study by finding sources of references from appropriate journals and theses regarding the effectiveness of calligraphy on maharah al-kitabah (calligraphy) memorizing the Koran. Data analysis, researchers used data collection techniques which were carried out through observation, direct interviews with resource persons at Mts Ma'had Tahfizhil Qur'an Islamic Center SU Foundation & documentation. The results of the study show that students have a fairly high interest in learning about maharah al-kitabah (calligraphy) but no skills in writing.